Health Literacy among Diabetic Patients Visiting the Outpatient Department of a Tertiary Care Hospital: A Cross-Sectional Study - Yadav, Ajay Kumar; Basnet, Lila Bahadur; Budhathoki, Shyam Sundar; Yadav, Ashok; Shrivastav, Vijay; Panthi, Sagar; Acharya, Rochana; Yadav, Gopal Kumar; Malla, Gyanendra Bahadur (Journal of BP Koirala Institute of Health Sciences, 2023)
Background: Diabetes Mellitus is a metabolic syndrome characterized by hyperglycemia either due to defective insulin secretion or defective insulin action or both. It is estimated to become the 7th leading cause of death by 2030. Health literacy play a significant role in self-care, adherence to medication and clinical outcomes in diseased individual. The objective of this study is to find the prevalence of poor health literacy among the diabetic patients visiting the outpatient department of a tertiary care hospital. Methods: A descriptive cross-sectional study was conducted among 422 diabetic patients visiting the outpatient department of a tertiary care hospital from July 2020 to Jan 2021. Ethical approval was obtained from the Institutional Review Committee (Reference number: IRC/1805/020). Patients aged ≥18 years, irrespective of gender, diagnosed with Diabetes Mellitus at least 3 months before and presenting to the outpatient department for complications or follow-up were included in the study. Convenience sampling was used. Result: Among 422 diabetic patients, poor health literacy was obtained among 165 (39.09%) (34.49-43.69 at 95% Confidence Interval). Low adherence to anti-diabetic medication was seen in 78 (47.27%) patients with majority 94 (56.97%) patients having diabetic range HbA1C level and a poor knowledge on diabetes. Conclusion: There is poor health literacy among diabetic patients that is reflected in low adherence to anti-diabetic medication and overall diabetic self-care. Targeted intervention for health promotion of diabetic patients might be needed.